Sort and Manage Huge Amounts of Unorganized Data Using Data Mining and Neural Networks: Exploring Advanced Methods for Sorting and Controlling Massive Amounts of Unstructured Data (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The exponential growth of unstructured data presents a formidable challenge to organizationsseeking valuable insights and actionable information. This paper explores innovative methods forsorting and controlling massive amounts of unstructured data through the integration of data miningtechniques and neural networks. The first part of this study delves into the significance of unstructureddata, outlining its sources, complexities, and potential value. It underscores the limitations of traditionaldata management approaches and highlights the need for advanced methodologies to extractmeaningful patterns and knowledge. Data mining, a fundamental component of this research, isexamined in depth. Various data mining techniques, such as clustering, classification, and associationrule mining, are explored, with a focus on their adaptability to unstructured data. Additionally, wediscuss the role of feature engineering and dimensionality reduction in enhancing the efficiency of datamining processes.